Synthesis and concanavalin A binding properties of alpha-D-mannopyranoside glycomimetics. - Abourahma, Heba. (University of Ottawa (Canada), 1999)
Glycomimetics of alpha-D-mannose were synthesized by derivatizing it at the 1-, 2-, and 6-positions. The synthesis of a series of known aryl alpha-D-mannopyranosides and novel aryl thio-alpha-D-mannopyranosides using Lewis acid catalysis is described. The method affords the desired products in very good yields (61--76%). Synthesis of the corresponding, novel arylsulfinyl alpha-D-mannopyranosides and arylsulfonyl alpha-D-mannopyranosides by conventional mCPBA oxidation is also described. The inhibitory effect by the C-1 modified compounds mentioned above on the binding of concanavalin A to yeast mannan was evaluated by ELLA and is reported. Aryl thio-alpha-D-mannopyranosides proved to be better inhibitors than the analogous aryl alpha-D-mannopyranosides. Arylsulfinyl alpha-D-mannopyranosides and arylsulfonyl alpha-D-mannopyranosides are better inhibitors than the corresponding aryl alpha-D-mannopyranosides but poorer inhibitors than the corresponding sulfides, except for p-methoxyphenylsulfonyl 1-thio-alpha-D-mannopyranoside which proved to be the most potent inhibitor of all the above tested compounds. Derivatization of methyl alpha-D-mannopyranoside to methyl 6-amino-6-deoxy-alpha-D-mannopyranoside, methyl 2-O-alkyl-alpha-D-mannopyranosides (alkyl = Me and Bn) and methyl 6-amino-2-O-alkyl-6-deoxy-alpha-D-mannopyranosides (alkyl = Et and Bn) is also described. The inhibitory effect of the first and latter series on the binding of Concanavalin A to yeast mannan was evaluated by ELLA and is reported. Modification of alpha-D-mannose at the 2- and 6-positions decreased the inhibitory effect of the binding of Concanavalin A to yeast mannan.
Keywords: Chemistry, Organic.